Metabolic, Biochemical and Histopathological Studies to Explore the Calcium Role in Antagonizing Gentamicin . Toxic Side Effect in Rats - Abbass, Duraid Abdulhadi; Ubaid, Khalid Ali (The Iraqi Journal of Veterinary Medicine, 2004)
Twenty rats were divided equally into four groups, housed separately in special metabolic cages. Animals of first, second and third group injected S.C. with gentamicin sulphate alone at a dose of 5mg/Kg (T) or as a mixture with calcium at a dose of 7.5 mg/Kg injected S.C. (T2) or separately with calcium given orally at a dose of 22.5 mg/Kg (T3). The fourth group considered as a control and injected S.C. with distilled water (C). The experiment includes samples analysis of sample of one week pre and post treatment and three weeks daily treatment. The results showed significant changes in studied parameters proportional with treatment period in animals of first group (Ti) in comparison with other groups expressed metabolically as a decline in body weight, increase in daily urine volume, biochemical as increase in serum creatinine, BUN, AP, AST, as well as histopathological changes in kidney nephrons and tubules. Calcium therapy whether as a mixture (T2) or alone (T3) gave nearly complete protection against gentamicin toxicity in the first and second week and incomplete one in the third week of treatment that could be attributed to the competitive interaction between calcium and gentamicin due to the similarity in charges and binding site that may cause a decline in gentamicin disposition in the target organ and tissue cell and so reduce its toxic side effect.